PENGARUH LEVERAGE, TATA KELOLA DAN KARAKTERISTIK PERUSAHAAN PADA PERATAAN LABA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pramita Indraswari, I Gusti Agung Ayu; Indra Tenaya, G Agus (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Income smoothing is a way that made the management to reduce fluctuations in corporate profits. Practice is done so peratan profit performance of the company look more effective in the eyes of investors. The purpose of this study was to determine the effect of leverage, corporate governance and corporate characteristics on income smoothing.This study was performed on companies listed in the Stock Exchange 2011-2013. The number of samples taken as many as 36 companies included in the rating CGPI consecutively during the study period, with a purposive sampling technique. Data collected through secondary data. The analysis technique used is logistic regression, where the dependent variable in this study is peratan profits as measured by the Index Eckle's and the independent variable leverage, corporate governance and company characteristics. Based on the results of research conducted found that the leverage and corporate governance has no effect on income smoothing. However, the characteristics of the company have a significant effect on income smoothing on companies listed in Indonesia Stock Exchange 2011-2013
Keywords: Income Smoothing, Eckle' s index, Leverage, Governance and Company Characteristics